Development of virtual laboratory for A-level & ADFP science subjects / Dr. Suganthi Devadason, Prof. Madya Nazlinda Abdullah and Nesamalar Kantasamy - Devadason, Suganthi (Dr.); Abdullah, Nazlinda (Prof. Madya); Kantasamy, Nesamalar (2005)
Use of virtual experiments to supplement traditional classroom lectures is recommended by many researchers to increase interest, motivation, and retention, as well as to improve higher order thinking and reasoning skills of students. The effectiveness of a given simulation may depend upon when it is administered within an instructional sequence. In the present work computer simulation experiments were developed based on A-Level syllabus of Edexcel London Board of examination. The development of computer simulation experiment was carried out using MATLAB, a technical computing software. Simulink, a software package for modeling, simulating, and analyzing dynamic systems was also used to create the virtual experiments. MATLAB and Simulink were integrated so that simulation of physical models could be carried out using both the software simultaneously. GUIDE, the MATLAB Graphical User Interface development environment was used in creating graphical user interfaces (GUIs). This tool greatly simplified the process of designing and building GUIs. A-Level students of INTEC were exposed to an additional method of learning technique using computer-based virtual laboratory experiments. The present study was designed to determine whether the virtual experiments improve students' learning process of interference of light waves in Physics. The effectiveness of this method has been tested using a pre-test and a post-test. The students had previous hands-on experience of the experiment on interference in a Physics laboratory prior to this v study. The finding in this study suggests that computer-based virtual experiments can offer a suitable cognitive and constructive learning environment for students. It is suggested that effective integration of computer simulation into traditional lecture-lab activities could enhance the performance of the students. Students' response to the new instructional technology using computer simulated experiments was found out using a questionnaire. The responses to the questionnaire were statistically analysed and it is found that students were very much interested in doing virtual experiments and they were much benefited by these experiments.